VARIASI WAKTU PEMBUATAN SERUM TERHADAP KADAR HDL KOLESTEROL - Etikah Masitoh; Freddy Agamonanza (Ensiklopedia of Journal, 2025)
High density lipoprotein (HDL) cholesterol is one of the lipoprotein components that plays an important role in transporting cholesterol from tissues to the liver. HDL cholesterol levels are measured using serum obtained from blood after the clotting process. Clotting times that do not follow the procedure can affect serum quality and the accuracy of test results. This study aims to determine the differences in HDL cholesterol levels based on variations in blood clotting time before centrifugation. This study is an experimental study with three treatments, namely blood clotting for 5 minutes, 10 minutes, and 15 minutes before centrifugation. Normality was tested using Shapiro-Wilk, while differences between groups were tested using the paired sample t-test with the help of SPSS software. The average HDL cholesterol level in blood frozen for 15 minutes was 35.88 mg/dL, for 10 minutes was 31.00 mg/dL, and for 5 minutes was 29.00 mg/dL. The statistical test results showed a significant difference between 15 minutes and 10 minutes of freezing (p = 0.000) and between 15 minutes and 5 minutes of freezing (p = 0.000). Variations in blood clotting time significantly affect HDL cholesterol levels. A clotting time of 15 minutes before centrifugation produces more optimal HDL levels and is in line with standard procedures. Keywords : HDL cholesterol, clotting time, blood serum